Tax policy and formalization of the micro and small enterprises in Metropolitan Lima - Ramirez Campomanes, Clesy Rosilene (2023)
Objective: Determine the relation between tax policy and the formalization of the micro and small enterprises in Metropolitan Lima. Method: The quantitative approach was used, with a non-experimental, cross-sectional, and relational design as it allowed the variables to be associated. For this purpose, the Pearson's chi-square test was applied. The sample consisted of 384 micro and small enterprises. Results: Out of the 384 micro and small enterprises, 23.44% (90) responded that no tribute is difficult to pay and, despite the fact that 10.42% (40) answered that the taxes owed to the National Superintendence of Customs and Tax Administration were the most challenging to pay, as were municipal tributes with 27.08% (104), it was found that 64,85% (249) is covered by a tax regime, where the highest percentage belongs to the new RUS (simplified single regime) with 50.3% (193). Conclusion: The tax policy has a significant relation with the formalization of the micro and small enterprises in Metropolitan Lima.